Recurrent mitral regurgitation and left atrial aneurysm in a pediatric patent: A complex case of infective endocarditis - Muhammad Kamran Younis Memon; Prabhat Khakural; Sivakumar Sivalingam (Wolters Kluwer Medknow Publications, 2023)
A 6-year-old boy with a history of infective endocarditis (IE) presented with recurrent disease manifesting as left hip arthritis and severe mitral regurgitation. He developed a rare complication - a left atrial pseudoaneurysm. Despite the absence of classic fever and systemic symptoms, imaging revealed the recurrence and guided surgical repair. This case highlights the complexities of recurrent IE in children and underscores the importance of high clinical suspicion and imaging modalities like echocardiography for diagnosis and management.